2021
DOI: 10.1007/s10841-021-00337-4
|View full text |Cite
|
Sign up to set email alerts
|

To graze or to mow? The influence of grassland management on grasshoppers (Orthoptera) on a flood protection embankment in the Donau-Auen National Park (Austria)

Abstract: Introduction Most Central European grasslands crucially depend on land use, and thus there is a need to comparatively analyse the impacts of different types of land use management on grassland biota. Aims and methods We use grasshoppers (Orthoptera), which are the most important insect herbivores in grasslands, and assess the differences of grazing (sheep) and mowing on species abundance, richness, and composition. We use a river embankment in the National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…bicolor ), which is in the line with previous studies (e.g. Almásy, Essl, Berger & Schulze, 2021; Fumy, Löffler, Samways & Fartmann, 2020; Gardiner, 2018; Weiss, Zucchi & Hochkirch, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…bicolor ), which is in the line with previous studies (e.g. Almásy, Essl, Berger & Schulze, 2021; Fumy, Löffler, Samways & Fartmann, 2020; Gardiner, 2018; Weiss, Zucchi & Hochkirch, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…A study conducted in Austria on grasshoppers (Orthoptera) showed that the average number of species between mown and grazed areas was very similar, while they differed in terms of the number of individuals. The average abundance in grazed transects was about one-third lower than in mowed transects [68]. In a study carried out by Szyszko-Podgórska [59] on land with different economic uses, it was shown that the number of species did not differ much between mowed and unmowed fallow land.…”
Section: Discussionmentioning
confidence: 90%
“…The years 2015-2018 were the driest in recorded history in Central Europe (Buras et al 2020;John et al 2020) and, while the average temperatures rose by 1.1 °C compared to pre-industrial situation globally (World Meteorological Organization 2019), they regionally increased by 2.1 °C compared to mid-20 th century (Czech Hydrometeorological Institute 2022). The small-scale threats stem from the fact that currently practised interventions differ from those that maintained the biotopes in the past (Valkó et al 2018;Almásy et al 2021;Kuhn et al 2021). Light machine-mowing effects differ from those of manual mowing or low intensity grazing.…”
Section: Introductionmentioning
confidence: 99%